P084 Response to appendectomy in refractory Ulcerative Colitis appears based on two distinct inflammatory phenotypes. (30th January 2023) - Becker drs., M; Heuthorst, L; van Roest, M; van der Bilt, J; Buskens, C; Wildenberg, M
Abstract: Background: Appendectomy has been suggested to decrease the risk of disease flares in UC, but we recently showed that even in therapy refractory patients, appendectomy may improve symptoms in a subset of patients. Despite several hypotheses, the effector mechanism of this phenomenon remains unclear. In this study we characterized gene expression profiles of appendices from therapy refractory UC patients either responding or non-responding to appendectomy, with the aim to identify pathways involved in response as well as guide selection of patients who are optimal candidates for appendectomy. Methods: Appendix specimen from responders (N=10) and non-responders (N=10) to appendectomy for therapy refractory UC were included (COSTA-study NCT03912714 or off-label appendectomy). Endoscopic response was defined as steroid-free remission at 12 months without intensified medical treatment. The control group consisted of patients with acute appendicitis(N=2). Post-operative biopsies were taken from the appendix and the coecal base and snap frozen. RNA was isolated and expression profiling was performed using RNAseq. Results: Unsupervised clustering indicated two separate clusters, one containing a more stromal phenotype expressing ADH1B, IGFBP5, Desmin and FLNA and the other expressing a more intestinal/B cell phenotype (OLMF4, PIGR, CEACAM5 and IHGA2). Stainings for the presence of collagen (stromal) versus pancytokeratin (epithelial) confirmed this analysis on protein level. Both clusters contained subclusters of responders and non-responders. In both the 'responder' subclusters, markers of immune activation were increased, but the type of response differed between 'stromal responders' and 'epithelial responders'. In 'stromal responders' increased expression of acute phase genes was present (FABP4, ADIPOQ, SAA1 and CXCL8). In the 'epithelial responders', immune activity was more characterized by increased mitochondrial activation/oxidative phosphorylation. In both subclusters, non-responders lacked these immune activation markers. We also evaluated the expression of the differentiating genes in biopsies of the coecal bottom. Indeed, the coecal samples also largerly clustered according to response based on the gene expression profile of the matching appendices. Conclusion: Patients responding to appendectomy showed two distinct gene expression patterns, suggesting two separate mechanisms of action. Although in both cases it clearly identified the requirement of active immune responses for response, the identifying markers differed between the two groups. This finding has consequences for both further functional studies into the effector mechanism of appendectomy in UC, but also in future efforts to identify patients suitable for this surgery.